Gallbladder ascariasis: a case report and review of literature - Janjua, Azwa; Sarwar, Muhammad Zeeshan; Farooq, Muhammad Shahid; Iftikhar, Sadaf; Naqi, Syed Asghar (International Surgery Journal, 2021)
Ascaris Lumbricoides uncommonly presents as a cholecystitis due to anatomical considerations. Despite that it presents 2.1% of the hepatobiliary ascariasis. Patients usually have vague symptoms of vague abdominal pain sometimes with fever, mimicking cholecystitis. Ultrasonography (USG) helps in definite diagnosis. We present a case of 50 years old female with gallbladder ascariasis for which cholecystectomy was done successfully.